The Estimation of Maximum Discharge Pipeline’s Length for Dredge Pump - Vera Vera (Indonesian Mining and Energy Journal, 2019)
A Cutter suction dredger is an important piece of mining equipment that is used by PT Timah, Tbk to conduct mining operations in the waters of the coast of Bangka Island. These operations involve complex offshore excavation activities, where materials containing tin ore are removed from below the shallow seafloor and then later transported to the stockpile with a floating pipe before processed at a washing plant. The process of moving these excavated materials into the washing plant presents a unique difficulty because of the long gap between a Cutter Suction Dredger and the stockpile – one that is solved with an attachment known as a dredge pump. The dredge pump plays a critical role as a variable in transporting the materials. This research was conducted to test the capability of the dredging pump’s hauling distance during the transporting process to match it with the target of rate soil displacement to the stockpile--that the mining operations would run as efficiently as possible. Also, this research used a quantitative approach method to calculate the performance of the dredging pump, which includes the rate of soil displacement in comparison to the distance between the cutter suction dredger and the stockpile. Based on the estimation of the distance during material transporting in order to attain the production target, the average result obtained for 10% solid concentration with the specificgravity between 2,68-7,0 is 8.256,85 m.